2019
DOI: 10.1097/md.0000000000014617
|View full text |Cite
|
Sign up to set email alerts
|

Development of prognostic signature and nomogram for patients with breast cancer

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…Nomograms have been widely used in clinical oncology as reliable tools for estimating numerical probabilities for individual patients by incorporating and illustrating important prognostic factors . This has been demonstrated in several types of cancers, including breast, lung, and gastric cancers, and the predictions of these nomograms may be more accurate than those based on the traditional TNM staging systems for various tumor types . Furthermore, we have thus far found relatively few nomograms for predicting survival in patients with stage II‐III CRC.…”
Section: Introductionmentioning
confidence: 99%
“…Nomograms have been widely used in clinical oncology as reliable tools for estimating numerical probabilities for individual patients by incorporating and illustrating important prognostic factors . This has been demonstrated in several types of cancers, including breast, lung, and gastric cancers, and the predictions of these nomograms may be more accurate than those based on the traditional TNM staging systems for various tumor types . Furthermore, we have thus far found relatively few nomograms for predicting survival in patients with stage II‐III CRC.…”
Section: Introductionmentioning
confidence: 99%
“…Powell et al (2018) demonstrated that CEACAM5 was a clinically relevant driver of breast cancer metastasis. NKAIN1 is associated with OS in breast cancer (Su et al, 2019). DSCAM-AS1 promotes tumor growth in breast cancer by reducing miR-204-5p and upregulating RRM2 (Liang et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, many biomarkers for breast cancer have been developed. A study developed a prognostic signature for the 19 gene associated with clinical prognosis in patients with BRCA (Su, Miao, Ye, Cui, & He, 2019). In addition, BCL2 and CD82 are both considered as potential and reliable biomarkers for breast cancer diagnosis (Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%